The Problem of Reading Habits of Children and The Youth: An Assessment of the Functionality of School Libraries - İsmail Akman; Nuran Akman (Türk Kütüphaneciliği)
Education is a process that begins in the family and supported by different institutions in the progressive stages. One of the most important of these institutions is school libraries. School libraries are vital to supporting and shaping the curriculum and the cultural development of the individual from an early age. While taking into account the numerical situation of school libraries, which are closely related to education, the quality of the school libraries should not be ignored. The quality of the school-library relation is directly proportional to the nature of both elements. Within the scope of this study, the quantitative and qualitative aspects of school libraries in Turkey are discussed in general terms and the steps to be taken for a quality educational-library interaction are discussed.